Abyssal Transport Variations in the Southwest South Atlantic: First Insights From a Long-Term Observation Array at 34.5°S - Valla, Daniel; Piola, Alberto Ricardo; Meinen, Christopher S.; Campos, Edmo (Geophysical Research Letters)
The zonal structure and time variability of the abyssal flow (below 3,000 dbar) in the South Atlantic western boundary is investigated using a combination of moored observations and simultaneous hydrographic/velocity sections at 34.5°S during 2009–2018. Moored direct velocity measurements near the bottom show strong variability with a peak-to-peak range exceeding 80 cm/s and dominant signals at times scales of 1–2 months. Daily time series of the meridional absolute geostrophic volume transport computed from the moorings reveals a highly energetic record with a temporal standard deviation of 8.3 Sv and peak-to-peak variations of 49 Sv, suggesting a significant contribution of the abyssal layer flows to the Deep Western Boundary Current time variability. The absolute transport is mostly driven by barotropic changes that are dominated by variations in the bottom pressure ~650 km away from the continental slope. Fil: Valla, Daniel. Ministerio de Defensa. Armada Argentina. Servicio de Hidrografía Naval; Argentina. Instituto Franco-argentino sobre Estudios del Clima y sus Impactos; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Ciencias de la Atmósfera y los Océanos; Argentina Fil: Piola, Alberto Ricardo. Ministerio de Defensa. Armada Argentina. Servicio de Hidrografía Naval; Argentina. Instituto Franco-argentino sobre Estudios del Clima y sus Impactos; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Ciencias de la Atmósfera y los Océanos; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Meinen, Christopher S. Atlantic Oceanographic and Meteorological Laboratory; Estados Unidos Fil: Campos, Edmo. Universidade de Sao Paulo; Brasil. American University Of Sharjah.; Emiratos Árabes Unidos